2021
DOI: 10.1002/jsfa.11658
|View full text |Cite
|
Sign up to set email alerts
|

Changes in protease activity during fermentation of fish sauce and their correlation with antioxidant activity

Abstract: BACKGROUND Antioxidant activity has been found in fermented fish sauce. In this experiment, the properties of endogenous protease and antioxidant activity were studied in anchovy sauce during fermentation. The correlation between protease activity and antioxidant activity in fermented anchovy sauce was analyzed using the partial least squares (PLS) method. RESULTS The results showed that at least four proteases were present in the endogenous enzyme solution, and the optimum pH values were 2.5, 5.5, 9.0, and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…DPPH, a kind of stable free radical, is widely used to evaluate the free radical scavenging activity of natural compounds 29 . The reducing power of a substance could also reflect its antioxidant activity: the higher the reducing power of a substance, the stronger is its antioxidant activity 48 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DPPH, a kind of stable free radical, is widely used to evaluate the free radical scavenging activity of natural compounds 29 . The reducing power of a substance could also reflect its antioxidant activity: the higher the reducing power of a substance, the stronger is its antioxidant activity 48 .…”
Section: Resultsmentioning
confidence: 99%
“…DPPH radical scavenging activity DPPH radical scavenging activity of PSSS was measured according to the method described by Bu et al, 29 with some modifications. Aliquots of 2 mL PSSS solution (20 g L −1 ) were added to 2 mL of 0.1 mmol L −1 DPPH-alcohol solution.…”
Section: Determination Of Antioxidant Active Substances and Antioxida...mentioning
confidence: 99%
See 1 more Smart Citation
“…The diverse endogenous enzymes and microbial enzymes in fermented fish products can be isolated and used as commercial enzyme products to support human health (e.g., protease supplements as digestion aids). Bu et al found that serine protease and trypsin can be obtained from fish sauce (Bu et al, 2022). Healthpromoting probiotic microorganisms can be obtained from fermented fish.…”
Section: Microbial-enabled Enrichment Of Bioactive Substances and Pro...mentioning
confidence: 99%
“…Bu et al. found that serine protease and trypsin can be obtained from fish sauce (Bu et al., 2022). Health‐promoting probiotic microorganisms can be obtained from fermented fish.…”
Section: Regulation Of Microbiota To Modulate the Generation Of Flavo...mentioning
confidence: 99%